Rethinking the Relationship between Milk Drinking and Population Health Outcomes - Nurrachmi, Rininta (Tamkin Jurnal Pemberdayaan Tazkia, 2024)
Dairy products are important ingredients for healthily and balanced diet. Past research often points to a positive relationship between milk drinking and population health outcomes. However, attempts to conceptualize the relationship between milk drinking and health outcomes are inconclusive. Hence, this paper aims to aid understanding and explaining the relationship between intake of milk and dairy products with population health outcomes based on existing studies within the period of 2001 until 2024 using Cardiovascular diseases (CVD) as indicator of health outcomes. The methodology of our paper is qualitative in nature and adopts methods of library research and critical content analysis. An introduction shows that there are benefits of consuming milk on human health. The result indicates that regular intake of milk could potential lower the risk of cardiovascular diseases (CVDs) based on scientifical research in several countries. With many type of milk, people need to adjust which milk that suitable and beneficial for their body based on its nutrition.